Las funciones ejecutivas como predictoras del nivel de pericia en jugadores de baloncesto - Francisco Alarcón (Revista de Psicología del Deporte, 2017)
teraction Sports are developed in extremely variable, unpredictable contexts, which means that the level of entropy is very high. In these environments, where decision making is decisive for sporting success, the participation of the central executive plays a key role. The aim of this study was to explore the potential importance of executive functions such as predictive value of the level of expertise of basketball players. A total of 34 men basketball players, of whom 12 belonged to a professional team of the ACB league ( M = 25.2 years), 12 a semi-pro team of the EBA league ( M = 20.7 years) and 10 of a regional amateur league team ( M = 22.7 years) were evaluated. Design Fluency Test was used for cognitive flexibility and Stroop interference test for the inhibitory capacity. Differences between the means of the ACB players and those of the other two groups, but not between semi- professional and amateurs were found. The results show a greater cognitive flexibility of professional basketball players over non professional players but instead does not distinguish between groups when referring to the inhibitory capacity. Considering that the first test also measures working memory and inhibitory capacity, the overall results point to the importance of executive functions in basketball and are consistent with those of previous studies indicating that elite athletes compared to sub-elite or novice have superior cognitive performance, although in this case highly specialized.